Blinding and bias in randomized controlled trials: when to measure the effectiveness of blinding. (30th September 2019) - Copeland, Lisa; Edwards, Priya; Sakzewski, Leanne; Thorley, Megan; Kentish, Megan; Ware, Robert S; Boyd, Roslyn N
Abstract : This article is commented on by Day on page 159 of this issue.